Control System Performance Analysis of Boiler’s Main Parameters in Steam Power Plant - Agus Yogianto, Tri Wahyu O Putri , Septianissa Azzahra (International Journal of Advanced Science and Technology, 2020)
Steam Power Plant has been implementing the usage of non-oil fuel (natural gases) as itsfuel. Like another general energy conversion machines, the efficiency aspect becomes thepriority, thus it needs a control system that is able to control the energy conversionprocess optimally. The efficient boiler performance is determined by optimal controlsystem in its boiler system. Therefore, in this study discusses the performance of boilermain parameters that associated with the boiler control system at Steam Power Plant PT.PJB UP Muara Karang. This research was done by observing the main parameters ofboiler then analysing those parameters based on its variance and error value. From theanalysis, the parameter that has the largest variance is furnace pressure, which is around21. A quite large variance in loop furnace pressure because the combustion chamberpressure does not have setpoint, so it is very dependent on the dynamics that occur in thecombustion chamber itself. While the errors of the main parameters have relatively smallerrors below the 2% limit. In general, it can be said that the performance of the mainparameters of the boiler as a result of the work of the control system shows goodperformance.